Comorbidities in cerebral palsy: a patient registry study. (4th July 2019) - Hollung, Sandra J; Bakken, Inger J; Vik, Torstein; Lydersen, Stian; Wiik, Robert; Aaberg, Kari M; Andersen, Guro L
Abstract : Aim: To describe the total burden of disease in individuals with cerebral palsy (CP) in Norway. Method: A comprehensive set of disorder categories were extracted from the Norwegian Patient Registry using International Statistical Classification of Diseases, 10th Revision diagnosis codes for individuals born between 1996 and 2010 who received specialist healthcare between 2008 and 2017 (0–21y). Individuals with CP were identified through a validation study in cooperation with the Cerebral Palsy Registry of Norway. Risk differences (proportions of individuals recorded with each disorder) were used to compare individuals with CP with the general population without CP. Results: The study included 966 760 individuals. Among these, 2302 (0.24%) had CP (1330 males, 972 females). Of the individuals with CP, 95.0% were recorded with one or more comorbidity, and the risks of medical, neurological, and mental/behavioural disorders were higher compared with the risks in the general population. The most common neurological and mental/behavioural disorders were cocausal, i.e. attributed to the same injury to the developing brain that caused CP, while medical disorders were most often complications of CP or coincidentally co‐occurring with CP. Interpretation: Individuals with CP have a considerably higher burden of medical, neurological, and mental/behavioural disorders compared with the general population, including disorders that are not directly caused by, or complications to, the brain injury. What this paper adds: Nearly all individuals with cerebral palsy (CP) had one or more comorbidity. Fifty‐two per cent had at least one comorbidity attributed to the same cause as CP, complications of CP, and coincidentally co‐occurring with CP. Risks of medical, neurological, and mental/behavioural disorders were considerably higher than in the general population. What this paper adds: Nearly all individuals with cerebral palsy (CP) had one or more comorbidity. Fifty‐two per cent had at least one comorbidity attributed to the same cause as CP, complications of CP, and coincidentally co‐occurring with CP. Risks of medical, neurological, and mental/behavioural disorders were considerably higher than in the general population. Video Podcast: https://www.youtube.com/watch?v=EzswCqo6hyc&feature=youtu.be